Development Instrument Evaluation Mathematics HOTS -Based for Prospective Junior High School Teachers - Asmarani, Dewi; Zahroh, Umy (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Higher-order thinking skills (HOTS) are essential for meeting the challenges of the 21st century. Therefore, these skills must be possessed by every individual engaged in the learning process. Students, as learners, need frequent practice to develop these skills. To facilitate this, prospective teachers should be capable of designing assessment instruments that foster higher-order thinking. However, in practice, teachers often struggle to create such instruments effectively, as it is a complex task. This study was initiated to address that challenge. It employed a research and development (R&D) approach using the 4D model: define, design, develop, and disseminate. The research subjects were 15 prospective mathematics teachers who developed HOTS-based test items, which were then tested on 79 seventh-grade students at Darul Akhwan International Junior High School. The developed items were evaluated for their validity and practicality through construct and empirical validity tests. The practicality was further assessed using reliability tests, item difficulty levels, and discrimination indices. The results showed that the instrument achieved 100% validity based on expert judgment. The reliability test yielded an rcount=0.659r_{count} = 0.659rcount​=0.659, which exceeds the rtable=0.2213r_{table} = 0.2213rtable​=0.2213; thus, the instrument is considered reliable. The discrimination index analysis revealed that 60% of the items were in the “fair” category, while the remaining 40% were categorized as “good.” Meanwhile, the difficulty level analysis showed that 15% of the items were “very difficult,” 65% were “difficult,” and 20% were “easy.” These results indicate that the instrument has an appropriate level of difficulty. In conclusion, the assessment instrument developed in this study is both valid and practical for evaluating students’ higher-order thinking skills.